2011
DOI: 10.1145/1989098.1989102
|View full text |Cite
|
Sign up to set email alerts
|

Online consumer market inefficiencies and intermediation

Abstract: This paper seeks to empirically unravel why consumers sometimes need to trust intermediaries in online markets. Notwithstanding assertions that online markets will eventually eliminate the need for intermediaries, intermediaries remain an active part of the online market landscape. This paper tries to understand this phenomenon from a view of a consumer lack of trust in online markets and seeks to unearth what ultimately causes a lack of consumer trust in online markets and the role played by intermediaries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Transparency is the extent to which relevant, timely, and reliable information is provided (Williams, 2005). Service process transparency, in particular, is the availability of complete knowledge of the service process to monitor and control a service (Datta & Chatterjee, 2011). For example, Welch, Hinnant, and Moon (2005) view service process transparency in the context of e-government as the extent to which a citizen can obtain a clear understanding of the working of a particular government process or service.…”
Section: Service Process Transparencymentioning
confidence: 99%
“…Transparency is the extent to which relevant, timely, and reliable information is provided (Williams, 2005). Service process transparency, in particular, is the availability of complete knowledge of the service process to monitor and control a service (Datta & Chatterjee, 2011). For example, Welch, Hinnant, and Moon (2005) view service process transparency in the context of e-government as the extent to which a citizen can obtain a clear understanding of the working of a particular government process or service.…”
Section: Service Process Transparencymentioning
confidence: 99%
“…Chatterjee and Datta (2011) targeted college students to create a virtual online shopping mall to examine the impact of online reviews and found that negative reviews had a significant impact on online trust and purchase intentions. On the other hand, Schiffman and Kanuk (2000) examined the motivation to express positive emotions and found that positive word-of-mouth (WOM) communication and other information concerning the reliability of businesses shared by trusted people play a crucial role in consumers' decision-making process.…”
Section: Motivational Factorsmentioning
confidence: 99%
“…In a time when citizens develop growing concerns regarding their personal data and private life protection , it becomes clear that privacy preservation can turn into a determinant of the diffusion and success of digital cooperation paradigms. Organizations have reached this realization; privacy concerns adversely affect consumers’ tendency toward engaging in electronic transactions , and hence, the absence of personal data protection measures can lead to reduced commercial activity. Moreover, the fact that the privacy domain during the last decades has become a legislated area further incentivizes enterprises to integrate protection mechanisms and enforce fair information manage‐ment practices.…”
Section: Introductionmentioning
confidence: 99%